2015
DOI: 10.1590/1807-1929/agriambi.v19n7p630-635
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation and fungicide application on disease occurrence and yield of early and late sown sunflower

Abstract: A B S T R A C TThe objective of this study was to evaluate the effect of irrigation and fungicide application on the occurrence of diseases and cypsela yield of two genotypes of sunflower. The experiments were carried out in Santa Maria-RS, during the regular season in 2007 and the late season, in 2008. Plants were sown on 04/09/2007 and 21/01/2008, in a completely randomized design, with four replicates. A 2 x 6 factorial scheme was used, with the sunflower genotypes Aguará 03 and Hélio 358 and six fungicide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…In the cited study, relative humidity was higher in the early (72-97%) than late rainy season, which increased the area under the disease-progress curve (AUDPC) and the disease severity index (DSI). Maldaner et al [60] examined the effect of irrigation and fungicides on the prevalence of infections and yields in two sunflower genotypes. They found that irrigation increased sunflower yields, but only in periods when weather conditions hindered the development of diseases caused by Alternaria spp.…”
Section: Mycological Analyses Of Tubers and Aerial Plant Partsmentioning
confidence: 99%
“…In the cited study, relative humidity was higher in the early (72-97%) than late rainy season, which increased the area under the disease-progress curve (AUDPC) and the disease severity index (DSI). Maldaner et al [60] examined the effect of irrigation and fungicides on the prevalence of infections and yields in two sunflower genotypes. They found that irrigation increased sunflower yields, but only in periods when weather conditions hindered the development of diseases caused by Alternaria spp.…”
Section: Mycological Analyses Of Tubers and Aerial Plant Partsmentioning
confidence: 99%
“…The variable that influenced the increase in severity was the additional artificial leaf wetness duration immediately after the pathogen distribution on the plants in the area as the air temperature and rainfall conditions were the same for all treatments. Sentelhas et al (1996), Loose et al (2012) and Maldaner et al (2015) also found a correlation between leaf wetness and the alternaria leaf blight, with increased disease severity in greater leaf wetness condition. Furthermore, Leite and Amorim (2002a) observed an increase in the lesion severity and density of alternaria leaf blight in sunflower with increased leaf wetness duration in a controlled environment.…”
Section: Discussionmentioning
confidence: 90%
“…Rainfall is one of the factors that most act on pathogen dispersion, enabling the beginning of a new cycle in a larger area and accelerating disease spreading (Agrios, 2004). Sentelhas et al (1996), Loose et al (2012) and Maldaner et al (2015) also verified that the condition of greater rainfall favors the septoria leaf spot in sunflower. Thus, we also observed an accelerated growth of the septoria leaf spot in a greater rainfall condition (Figure 1), which conditioned the increase in the observed disease severity.…”
Section: Discussionmentioning
confidence: 98%
“…Menzies 1967, Rotem and Palti 1969, Dixon et al 2015, De Villiers et al 2017, Avila et al 2019, Swett 2020) through increased canopy moisture, changes in stomatal conductance, and microcracking, although in some instances reduced water stress may also enhance disease resilience (Swett 2020). Potential mitigation strategies include more targeted fungicide use and the extensive use of durable rust-resistant varieties and drip irrigation systems in regions where irrigation is to take place (Sanogo 2004, Daugovish et al 2012, Maldaner et al 2015, Swett 2020. Given the importance of irrigation as an adaptation strategy for climate change and improved food security, it is recommended that irrigation expansion plans be accompanied by risk assessment analyses to identify any associated mitigations also required.…”
Section: Discussionmentioning
confidence: 99%